If f(x)=3x+10x and g(x)=4x-2 find (f+g)(x)
A:3x+6x+2
B:17x-2
C:3x+14x-2
D:3x-6x+2
1 answer:
Answer:
3x^2+14x-2 if you meant f(x)=3x^2+10x and g(x)=4x-2
and I think C was meant to read 3x^2+14x-2
Please correct me if I have mistranslated. Thank you kindly.
Step-by-step explanation:
I kind of wonder if you meant f(x)=3x^2+10x and g(x)=4x-2.
(f+g)(x)=f(x)+g(x)
=(3x^2+10x)+(4x-2)
=3x^2+10x+4x-2
=3x^2+(10x+4x)-2 I paired 10x and 4x together because they are like terms
=3x^2+14x-2
You might be interested in
Answer:
I hope this helps:))
Step-by-step explanation:
Answer:
5.6
Step-by-step explanation:
Divide :)
Answer:
a balloon ?
Step-by-step explanation:
Answer:
The answer is Option one.
Step-by-step explanation:
X+x= 2x and -1 - 1 = -2
Answer:
Kerry should cut it into 1 1/3 pieces
Step-by-step explanation:
divide the total by the parts you want to get the length of a part
8/6=4/3